Negotiating the boundaries between the formal and the informal: An experienced teacher's reflective adaptations of informal learning in a keyboard class for at-risk students. Issue 3 (30th June 2016) - Costes-Onishi, Pamela
Abstract : The objective of this study is to address the important questions raised in literature on the intersections between formal and informal learning. Specifically, this will be discussed within the concept of 'productive dissonance' and the pedagogical tensions that arise in the effort of experienced teachers to transition from the formal to the informal. This case study discusses the issues that ensue when strict demarcations between formal and informal are perceived, and demonstrates that the former is vital to the facilitation of the latter. The blurring of formal and informal pedagogical approaches has shown that the concept of 'critical musicality' becomes more apparent in student learning and that engagement increases especially among at-risk students.